Distinct retinoid X receptor-retinoic acid receptor heterodimers are differentially involved in the control of expression of retinoid target genes in F9 embryonal carcinoma cells. - Chiba, H (1997)
The F9 murine embryonal carcinoma cell line represents a well-established system for the study of retinoid signaling in vivo. We have investigated the functional specificity of different retinoid X receptor (RXR)-retinoic acid (RA) receptor (RAR) isotype pairs for the control of expression of endogenous RA-responsive genes, by using wild-type (WT), RXR alpha(-/-), RAR alpha(-/-), RAR gamma(-/-), RXR alpha(-/-)-RAR alpha(-/-), and RXR alpha(-/-)-RAR gamma(-/-) F9 cells, as well as panRXR and RAR isotype (alpha, beta, and gamma)-selective retinoids. We show that in these cells the control of expression of different sets of RA-responsive genes is preferentially mediated by distinct RXR-RAR isotype combinations. Our data support the conclusion that RXR-RAR heterodimers are the functional units transducing the retinoid signal and indicate in addition that these heterodimers exert both specific and redundant functions on the expression of particular sets of RA-responsive genes. We also show that the presence of a given receptor isotype can hinder the activity of another isotype and therefore that functional redundancy between retinoid receptor isotypes can be artifactually generated by gene knockouts.